2015
DOI: 10.2147/opth.s80043
|View full text |Cite
|
Sign up to set email alerts
|

Making the diagnosis of Sjögren’s syndrome in patients with dry eye

Abstract: Sjögren’s syndrome (SS) is a chronic and progressive systemic autoimmune disease that often presents initially with symptoms of dry eye and dry mouth. Symptoms are often nonspecific and develop gradually, making diagnosis difficult. Patients with dry eye complaints warrant a step-wise evaluation for possible SS. Initial evaluation requires establishment of a dry eye diagnosis using a combination of patient questionnaires and objective ocular tests, including inflammatory biomarker testing. Additional work-up u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 68 publications
(105 reference statements)
5
56
0
Order By: Relevance
“…Schirmer’s test I is commonly used to diagnose dry eye, but because it is performed without anesthesia, it evaluates not only the amount of tear storage and basal secretion but also reflective secretion. This evaluation method is more pertinent in Sjögren’s syndrome and other conditions in which the lacrimal gland is damaged and tear secretion is decreased 17. As described earlier, we concluded that VApal mainly acted on the corneal and conjunctival epithelial layer of the ocular surface, not on the lacrimal glands or via a mechanism that increased tear production.…”
Section: Discussionsupporting
confidence: 63%
“…Schirmer’s test I is commonly used to diagnose dry eye, but because it is performed without anesthesia, it evaluates not only the amount of tear storage and basal secretion but also reflective secretion. This evaluation method is more pertinent in Sjögren’s syndrome and other conditions in which the lacrimal gland is damaged and tear secretion is decreased 17. As described earlier, we concluded that VApal mainly acted on the corneal and conjunctival epithelial layer of the ocular surface, not on the lacrimal glands or via a mechanism that increased tear production.…”
Section: Discussionsupporting
confidence: 63%
“…Tear function tests [40,41] are used to distinguish between ADDE and EDE, as mentioned above. Schirmer's test and tear meniscus assessment (tear lake) may help identify ADDE and distinguish it from EDE; the details of the differential diagnosis of dry eye have been reviewed in greater detail elsewhere [42,43]. The tear function index (TFI) and vital dye stains (Rose Bengal; lissamine green) are also used.…”
Section: Tests Commonly Used In the Assessment Of Ssmentioning
confidence: 99%
“…The patient was presumed to have early SS and referred back to a rheumatologist for further care. He was treated with oral hydroxychloroquine therapy and later treated Table 3 Traditional and novel biomarkers included in the Sjö diagnostic test; adapted with permission from Beckman et al [42] Diagnostic characteristics Traditional biomarkers [7] Anti-SS-A/Ro, anti-SS-B/La Not specific for SS; occurs in other autoimmune disorders, particularly SLE Antinuclear antibody (ANA) Titer C1:40 present in about two-thirds of SS patients [35] Rheumatoid factor (RF) Found in many rheumatic conditions but is not unique to SS…”
Section: The Sjö ò Testmentioning
confidence: 99%
“…Aqueous tear production was quantified by measuring the amount of wetting. Less than 5 mm of wetting is highly suggestive of aqueous tear deficiency, while 5-10 mm is equivocal (Hikichi et al, 1995;Shrestha et al, 2011;Beckman et al, 2015;Courtin et al, 2016).…”
Section: Schirmer Testmentioning
confidence: 99%
“…The timing of the appearance of the first randomly distributed dry spot of tear film is the tear BUT. A BUT of less than 10 s is considered abnormal (Brasche et al, 2001;Beckman et al, 2015;Courtin et al, 2016).…”
Section: Measurement Of Tear Butmentioning
confidence: 99%